The Influence of Social Media Use on Innovation Capabilities and Business Growth of MSMEs - Putra, Aditiya; Hardiansyah, Rian (Journal of Educational Management Research, 2025)
This study examines the effect of social media use on the innovation capabilities and business growth of MSMEs in Sumbawa Regency. The research method used is quantitative with a Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. Data was collected through a survey of active MSME players who use social media in their business operations. The analysis results indicate that the use of social media has a positive and significant impact on the innovation capabilities of SMEs, as reflected in their ability to produce innovative and adaptive products and services. Additionally, the use of social media also contributes positively and significantly to the growth of SMEs, both directly and indirectly through enhanced innovation capabilities. These findings confirm that social media is a strategic tool for expanding market reach, enhancing digital marketing, and strengthening the competitiveness of SMEs in the digital era. This study also emphasizes the importance of developing innovation capabilities as a mediator in strengthening SME business growth. The practical implications of this research are the need for increased training in social media utilization and the cultivation of an innovation culture among SME actors to optimize business growth and sustainability. This study contributes to the development of SME empowerment strategies, particularly in the context of digitalization in Sumbawa Regency.